ANALISIS PENGARUH IMPLEMENTASI GUGUS KENDALI MUTU TERHADAP KINERJA DAN KEPUASAN KERJA KARYAWAN MENGGUNAKAN MODEL PERSAMAAN STRUKTURAL - Sukwadi, Ronald (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
Product quality is one issue in business survival. One of quality strategies using group oriented isÂ known as Quality Control Circle (QCC). The aim of this research is to analyze the effect of theÂ implementation of QCC to the employeeâs work performance and satisfaction at PT PDP. The objectsÂ observed in this research were employees of PT PDP. The samples studied were 112 employees who areÂ currently undergoing QCC at Production Engineering, Production, Warehouse and Quality Control sections.Â The method used for data collection in this study is random sampling. The collected data is then furtherÂ analyzed using Structural Equation Modeling software AMOS 7.0. This research showes that QCC has directÂ effect on the employeeâs work performance and satisfaction, and employeeâs satisfaction also has directÂ influence on the employeeâs work performance.